An inverse latitudinal gradient in infection probability and phylogenetic diversity for Leucocytozoon blood parasites in New World birds. Issue 2 (29th October 2019) - Fecchio, Alan; Bell, Jeffrey A.; Bosholn, Mariane; Vaughan, Jefferson A.; Tkach, Vasyl V.; Lutz, Holly L.; Cueto, Victor R.; Gorosito, Cristian A.; González‐Acuña, Daniel; Stromlund, Chad; Kvasager, Danielle; Comiche, Kiba J. M.; et al.
Abstract: Geographic variation in environmental conditions as well as host traits that promote parasite transmission may impact infection rates and community assembly of vector‐transmitted parasites. Identifying the ecological, environmental and historical determinants of parasite distributions and diversity is therefore necessary to understand disease outbreaks under changing environments. Here, we identified the predictors and contributions of infection probability and phylogenetic diversity of Leucocytozoon (an avian blood parasite) at site and species levels across the New World. To explore spatial patterns in infection probability and lineage diversity for Leucocytozoon parasites, we surveyed 69 bird communities from Alaska to Patagonia. Using phylogenetic Bayesian hierarchical models and high‐resolution satellite remote‐sensing data, we determined the relative influence of climate, landscape, geography and host phylogeny on regional parasite community assembly. Infection rates and parasite diversity exhibited considerable variation across regions in the Americas. In opposition to the latitudinal gradient hypothesis, both the diversity and prevalence of Leucocytozoon parasites decreased towards the equator. Host relatedness and traits known to promote vector exposure neither predicted infection probability nor parasite diversity. Instead, the probability of a bird being infected with Leucocytozoon increased with increasing vegetation cover (NDVI) and moisture levels (NDWI), whereas the diversity of parasite lineages decreased with increasing NDVI. Infection rates and parasite diversity also tended to be higher in cooler regions and higher latitudes. Whereas temperature partially constrains Leucocytozoon diversity and infection rates, landscape features, such as vegetation cover and water body availability, play a significant role in modulating the probability of a bird being infected. This suggests that, for Leucocytozoon, the barriers to host shifting and parasite host range expansion are jointly determined by environmental filtering and landscape, but not by host phylogeny. Our results show that integrating host traits, host ancestry, bioclimatic data and microhabitat characteristics that are important for vector reproduction are imperative to understand and predict infection prevalence and diversity of vector‐transmitted parasites. Unlike other vector‐transmitted diseases, our results show that Leucocytozoon diversity and prevalence will likely decrease with warming temperatures. Abstract : Parasitic organisms must overcome ecological, environmental and evolutionary barriers to infect their hosts. Establishing how climatic, ecological and historical factors influence the diversity and transmission of pathogens within host communities is a central goal in disease ecology. In this study, the authors used phylogenetic Bayesian hierarchical models and high‐resolution satellite remote‐sensing data, to identify such barriers while testing a long‐standing hypothesis that infection pressures are higher at lower latitudes.